Design of timetable for airport coach based on ‘time–space’ network and passenger’s trip chain - Lu, Jing; Yang, Zhongzhen; Dong, Xiadan; Zhu, Xiaocong (Transport, 2018)
This paper designs the timetable for the airport coach which is a new access service provided by the airport with the purpose of attracting more passengers. Firstly, the ‘time–space’ network is constructed for analyzing the formation of the passengers’ trip chain; Secondly, the timetable design model is built with the aim to minimize the unit operation cost per transported passenger of the airport coach and a genetic algorithm with matrix coding is used for solving the model. In the model, the coach departure time and the flight schedule are connected with each other; the quality of the coach service and the passenger’s demand are both considered. Finally, the coach of Dalian airport in China is taken as an example to test the proposed method. Through solving the model and sensitivity analysis, we obtain a coach timetable for Dalian airport. The results show that the proposed model can provide a practical method to design the timetable for the airport coaches with ‘hub-and-spoke’ network.First published online 28 January 2015